POLA ASUH ANAK DALAM LINGKUNGAN KELUARGA POLRI (STUDI DI ASRAMA POLDA RIAU PEKANBARU) - Keke Dwi Sundari; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pattern foster the maintenance of a child that is how parents treat, educate, guide and discipline and protecting the child. Based on the above, then the problem can be formulated as follows: "How do child care in a family environment and the Police Are family upbringing affect the child's social relationships outside the hostel". Based on the formulation of the above problems, the purpose of this study was to determine how parenting within the family and the police to find out if family upbringing affect the child's social relationships outside the hostel. Democratic Parenting, parents are rational, always takes action on the ratio or thoughts. Parents of this type also is the reality of the child's abilities, do not expect exceeds the limit of their ability. Parents of this type also gives freedom to children, to train and perform an action and its approach to children is warm. In accordance with the problems and objectives that have been formulated, then the population in this study is the entire family who live in dormitories Police Polda Riau. The author takes a sample using purposive sampling totaling 30 households. This research data collection instruments such as questionnaires and documentation. In analyzing the data using quantitative descriptive method. The research results parenting parents in the family, the police amounted to 64.96% categorized into Parenting in the Police Families Good. Parenting applied in the national police family is Democratic Parenting. Parenting impact on the child's social relationships outside the hostel dominant done by children of their families is the dominant National Police be polite to older, give a smile to greet friends, and exchanged greetings with each other when each other. Based on the results of the analysis showed that the percentage of 67.1% is in the range of 61% -80% value. Shows that the categorization of Parenting Family Impact on Social Relations Children outside the hostel was included in the category of Good. Keywords: Parenting, Family